Behavioral and morphological contrasts on the reproduction of two prolonged breeders of the genus Physalaemus (Anura: Leptodactylidae) - Cajade, Rodrigo (2020)
The reproduction is one of the main events in the life of an organism, and anurans stand out among vertebrates because of the diversity of their reproductive strategies. We studied the reproduction of two syntopic species, Physalaemus aff. albonotatus and P. santafecinus, and comparatively described their reproductive activity pattern, advertisement calls, calling sites, daily calling activity, amplexus behavior, foam nests, and microhabitats in foam nests. In regards to the reproductive activity pattern, both species were defined as prolonged breeders. However, P. santafecinus exhibited a behavior like explosive breeders: it had a faster reproductive response against rains than P. aff. albonotatus. The calling activity was restricted exclusively to night hours in P. santafecinus, whereas P. aff. albonotatus called during both night and day. The advertisement calls of both species showed a rich harmonic structure, and were characterized by a bimodal harmonic dominance. The species differed significantly in microhabitat calling sites, foam nests, and microhabitats in foam nests. Namely, P. santafecinus frequently called and constructed its nests in sites more exposed than those of P. aff. albonotatus. The general differences in reproductive behaviors observed between the species principally agree with their different reproductive activity patterns.